2006
DOI: 10.1111/j.1601-1546.2009.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and sequelae of canal transportation

Abstract: Instrumentation of curved root canals is still a challenge even for skilled and experienced operators. During shaping of these canals, canal transportation, straightening, or canal deviation may occur. This paper describes different preparation outcomes as possible results of canal transportation, and the action of different root canal instruments when used in curved canals, and provides an overview of current in vitro and in vivo studies assessing canal transportation. In the second part of this paper, the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
54
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 99 publications
(205 reference statements)
0
54
0
1
Order By: Relevance
“…And the risk of transportation always increases in curved canals and with the increase of file size. Wider apical preparation might result in some canal straightening and undesirable weakening of the tooth structure, whereas minimal enlargement may leave tissue remnants and infected dentin behind 24. Thus, the Reciproc R25 file, the WaveOne primary reciprocating file, ProTaper F2, Profile #25 .06 and #25 K file were selected for this study.…”
Section: Discussionmentioning
confidence: 99%
“…And the risk of transportation always increases in curved canals and with the increase of file size. Wider apical preparation might result in some canal straightening and undesirable weakening of the tooth structure, whereas minimal enlargement may leave tissue remnants and infected dentin behind 24. Thus, the Reciproc R25 file, the WaveOne primary reciprocating file, ProTaper F2, Profile #25 .06 and #25 K file were selected for this study.…”
Section: Discussionmentioning
confidence: 99%
“…These differences in the centering ability of especially rotary NiTi instruments versus stainless steel hand instruments are even more pronounced when the final apical preparation is larger than size 30. Thus rotary NiTi instruments offer the opportunity to enlarge root canals to greater apical preparation sizes [23][24][25][26][27]. When viewed in total, these positive attributes would tend to support the speculation that the use of NiTi instrument may very well result in enhanced clinical outcomes.…”
Section: Introductionmentioning
confidence: 97%
“…Nonetheless, with the introduction of root canal instruments made from the superelastic alloy nickel-titanium the technical quality of root canal preparation has been steadily improving during the past years. Nickel-titanium (NiTi) hand as well as rotary instruments with tapers greater than the ISO-standard have been shown in numerous in vitro studies (for overviews see [22,23]) and in some clinical studies (Table 1) to enlarge and shape even severely curved root canal with fewer procedural errors than traditional stainless steel hand instruments. These differences in the centering ability of especially rotary NiTi instruments versus stainless steel hand instruments are even more pronounced when the final apical preparation is larger than size 30.…”
Section: Introductionmentioning
confidence: 99%
“…Ram (10) also observed that canals need to be enlarged to the diameter of a #40 file to ensure maximal contact of the irrigation fluid with the apical debris. However, the attainment of a larger apical diameter is challenging and can lead to more procedural errors (11). Instrumentation with nickel-titanium (NiTi) rotary files allows for greater efficiency and predictability and provides better centering in the canal than hand instrumentation with stainless-steel instruments (12)(13)(14).…”
mentioning
confidence: 99%